Strategic Design of Halal Canteens: Exploring the Zona KHAS Concept and Its Global Implications in University Environments - Umi Cholifah; Deasy Wulandari; Istikomah (Department of Sharia Economics Faculty of Islamic Economics and Business, Universitas Islam Syarifuddin Lumajang, Indonesia, 2025)
This study develops a strategic concept for halal canteens using the Zona KHAS (Halal, Safe, and Healthy Culinary Zone) framework, integrating halal assurance, food safety, health, and comfort in accordance with sharia principles. The research aims to create a strategic model for halal canteens in university settings, focusing on halal certification, food safety, and student Well-being. While the study is based on universities in Jember Regency, it also explores the broader applicability of the Zona KHAS framework in global contexts. Using a qualitative, exploratory approach, 21 canteens across six universities were observed. Data were collected through interviews, observations, and document analysis, and analyzed using NVivo 15. The study found that seven of twelve Zona KHAS criteria were met, with managerial professionalism and halal staff training requiring improvement. Key components identified for Zona KHAS implementation include halal certification, food safety, digital transactions, and supporting facilities. This model promotes sustainable campus development and enhances students' overall Well-being.